Cumulative adversity profiles among youth experiencing housing and parental care instability. (May 2019) - Crumé, Henry Joel; Nurius, Paula S.; Fleming, Christopher M.
Abstract: This study applies cumulative adversity and stress proliferation theories to examine risk and protective resource profiles of youth with three different levels of housing and parental care instability. Data derive from a state representative sample ( n = 27, 087) of school-based adolescent students. ANCOVA analyses identified significant differences in sociodemographic and psychosocial functioning variables for youth with 0, 1, or 2 forms of housing and parental care instability, with more deleterious functioning being observed among youth with greater levels of instability. Those experiencing either or both housing and parental care instability are more represented by males, sexual minorities, and youth of color; psychosocial risk and protective factors demonstrated consistent differences between instability groups. Dimensions of cumulative adversity operate with social marginalities (e.g., race, sexual minority status) relative to instability, with higher frequency of victimization, lower grades, diminished self-regulation capabilities and school engagement, weakened psychological health, and strained family and peer relationships. The paper discusses theorized mechanisms through which cumulative adversity conveys effects as well as implications for social work prevention and resilience-fostering strategies in schools and other youth-serving settings. Highlights: Youth instability in either housing or parental care is a growing concern in the U.S. and poses serious developmental risk. LGBT youth and youth of color experience housing and parental care instability at higher rates. Youth experiencing greater instability are distinguished by significantly poorer psychosocial and health functioning. Youth experiencing greater instability report poorer academic performance and less prosocial opportunities.